2020
DOI: 10.1590/1980-4415v34n66a06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la Faceta Epistémica del Conocimiento Didáctico- Matemático de Futuros Profesores de Matemáticas en el Desarrollo de una Clase Utilizando Funciones

Abstract: Resumen Se reportan los hallazgos de un trabajo realizado con cincuenta futuros profesores de licenciatura en matemática de una universidad pública colombiana. A partir de un seguimiento en su progreso de estudiantes a profesores, se analizaron sus dificultades en el desarrollo de clases con estudiantes de enseñanza media. Los resultados evidencian cierta facilidad en los futuros profesores en el reconocimiento de los elementos y las características de una función, pero algunas dificultades para conectar sus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…Semiotic representations are constructions through signs with which people externalise their mental representations (Duval, 2017), and registers are the containers that allow those representations to be configured (Amaya, 2020). They have their own rules and sign systems, although some rules and signs are shared with other registers.…”
Section: Semiotic Registers and Representationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Semiotic representations are constructions through signs with which people externalise their mental representations (Duval, 2017), and registers are the containers that allow those representations to be configured (Amaya, 2020). They have their own rules and sign systems, although some rules and signs are shared with other registers.…”
Section: Semiotic Registers and Representationsmentioning
confidence: 99%
“…Despite the importance of function as a curriculum articulator in mathematics study plans (Steele et al, 2013) and as a modelling tool, students and pre-service teachers present gaps and conceptual limitations in their learning (Amaya, 2020). Various studies (Even, 1998;Amaya et al, 2016;Bueno & Pérez, 2018) have reported difficulties in understanding associated with their teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahora bien, todos los países del mundo se han ajustado a modelos basados en la virtualidad y, por otro lado, el estudio de las matemáticas en particular ha tomado especial atención dadas las características y métodos de enseñanza que se han venido desarrollando durante el tiempo, Revista de Educación Mediática y TIC, 2022, 11(1) Romero-Chacín, J.L., Romero-Colmenares, J., Reyes-Contreras, R., Barboza-Arenas, L. A., & Romero-Parra, R. M. y donde la presencialidad se asume, en muchos casos, como un eje fundamental del proceso. En tal sentido, el cambio en la enseñanza de esta disciplina es eminente (Armas, 2020).…”
Section: Introductionunclassified